GENDUREN LINTAS AGAMA DI DAERAH TRASMIGRAN DALAM PERSPEKTIF SOSIAL DAN AGAMA (Studi Kasus di Desa Muara Jaya Sukadana Lampung Timur) - Muhammad Nur Amin (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2020)
The study discusses the transcendental gender in the transmigrant area in social and religious perspectives. In the midst of the spread of issues and cases of intolerance, both on a national and global scale. There is a trasmigrant area that has a unique tradition, in the form of inter-religious gender. This is interesting to discuss as an effort to revive the values of tolerance and religious harmony that is almost dim today. Through phenomenological research, it can be concluded that there are several factors that influence people to do this interfaith slendering, including; cultural, religious and social settings.